Enteral Nutrition Formula Selection: Current Evidence and Implications for Practice. (February 2015) - Brown, Britta; Roehl, Kelly; Betz, Melanie
Many new enteral nutrition (EN) formulas have been created over the past several decades with a variety of intended uses. Although each is intended to promote improved outcomes, research is often unclear and, in many cases, conflicting. It is important to note that EN products are considered medical foods by the U.S. Food and Drug Administration and therefore do not have to complete premarket review or approval and are not regulated to the same extent as pharmaceuticals. While standard EN formulas are designed to meet the basic macro- and micronutrient requirements of individuals who cannot meet nutrition needs orally, specialty EN products have been developed to exhibit pharmacologic properties, such as immune-enhancing formulas containing arginine, glutamine, nucleotides, and ω-3 fatty acids. With the vast number of products available, rising costs of healthcare, and the drive toward evidence-based practice, it is imperative that clinicians carefully consider research regarding use of specialty formulas, paying close attention to the quality, patient population, clinical end points, and cost to patient and/or facility.